A RETROSPECTION ON ECONOMIC DEVELOPMENT OF INDIA FROM COLONIAL TIMES TO 1991 AD: FROM BRITISH RAJ TO ECONOMIC LIBERALIZATION - Yadav, Kanishka; Mishra, Satendra Kumar (International Journal of Research -GRANTHAALAYAH, 2024)
This study undertakes a comprehensive retrospection of India’s economic development from colonial times up to 1991, which marks the commencement of significant economic reforms. During the colonial era, India’s economy was characterised by deindustrialization, exploitation of resources, and a focus on agricultural production for export, leading to economic stagnation and impoverishment. Post-independence, India’s economic trajectory was shaped by adopting Nehruvian socialism, characterized by state-led industrialization, strategic Five-Year Plans, and significant agrarian reforms aimed at reducing inequality and promoting self-reliance. The Industrial Policy Resolution of 1956, often referred to as India’s ’Economic Constitution, ’laid the groundwork for a mixed economy, emphasizing the development of heavy industries, expansion of the public sector, and cooperative sector growth. However, despite these efforts, the economy faced challenges such as inefficiency, slow growth, and resource misallocation. The economic landscape underwent a paradigm shift with the introduction of the New Industrial Policy of 1991, which marked a transition from a planned economy to a market-oriented one. This policy ushered in an era of liberalization, privatization, and globalization, aiming to correct structural distortions, enhance productivity, and integrate India into the global economy. Key reforms included the abolition of industrial licensing, encouragement of foreign direct investment, and deregulation of public enterprises, fundamentally transforming India’s economic environment. This retrospection highlights the evolution of India’s economic policies and their impacts, underscoring the interplay between state intervention and market mechanisms in shaping the nation’s development. The study provides a critical analysis of policy shifts, their socioeconomic implications, and the foundational changes that set the stage for India’s subsequent economic growth.